Polysialic acid sustains cancer cell survival and migratory capacity in a hypoxic environment - Elkashef, Sara M.; Allison, Simon J.; Sadiq, Maria; Basheer, Haneen A.; Ribeiro Morais, Goreti; Loadman, Paul M.; Pors, Klaus; Falconer, Robert A. (Scientific reports, 2016)
Polysialic acid (polySia) is a unique carbohydrate polymer expressed on the surface of NCAM (neuronal cell adhesion molecule) in a number of cancers where it modulates cell-cell and cell-matrix adhesion, migration, invasion and metastasis and is strongly associated with poor clinical prognosis. We have carried out the first investigation into the effect of polySia expression on the behaviour of cancer cells in hypoxia, a key source of chemoresistance in tumours. The role of polysialylation and associated tumour cell migration and cell adhesion were studied in hypoxia, along with effects on cell survival and the potential role of HIF-1. Our findings provide the first evidence that polySia expression sustains migratory capacity and is associated with tumour cell survival in hypoxia. Initial mechanistic studies indicate a potential role for HIF-1 in sustaining polySia-mediated migratory capacity, but not cell survival. These data add to the growing body of evidence pointing to a crucial role for the polysialyltransferases (polySTs) in neuroendocrine tumour progression and provide the first evidence to suggest that polySia is associated with an aggressive phenotype in tumour hypoxia. These results have significant potential implications for polyST inhibition as an anti-metastatic therapeutic strategy and for targeting hypoxic cancer cells.